Age in relation to comorbidity and outcome in patients with high-risk TIA or minor ischemic stroke: A Swedish national observational study. (March 2021) - Fasth, Oskar; Lesén, Eva; Appelros, Peter; Farahmand, Bahman; Hedberg, Jonatan; Ladenvall, Per; Mellström, Carl; Åsberg, Signild
Introduction: Recent trials report positive results for preventing vascular events with dual antiplatelet therapy (DAPT) in patients with high-risk TIA or minor ischemic stroke. We aimed to investigate this population regarding influence of age on vascular risk factors, hospital stay and mortality. Patients and methods: Data on patients aged 40–100 years with TIA or ischemic stroke in the Swedish Stroke Register during 2012–13 were linked with national registers. To identify patients with high-risk TIA (ABCD 2 ≥6) or minor ischemic stroke (NIHSS ≤5) eligible for DAPT, we excluded patients with atrial fibrillation, anticoagulant use, prior major bleeding, or unknown stroke severity. Findings: We identified 10, 053 potential DAPT-candidates (mean age 72.6 years, 45.2% female, 16.4% with TIA). With advancing age, most vascular risk factors increased. Antiplatelet treatment increased from 31.9% before the event to 95.5% after discharge. Within 1 year following index event, the proportion of patients with ≥1 re-admission increased with age (29.2% in 40–64 year-olds; 47.2% in 85–100 year-olds). All-cause death per 100 person-years was 6.9 (95% CI 6.4–7.4) within 1 year, and highest in the first 30 days (15.2; 95% CI 12.8–18.2). For each year of increased age, the risk of death increased with 3.5% (p = 0.128) in patients 40–64 years and with 11.8% (p < 0.001) in those ≥85 years. Conclusions: While in theory representing a subset of patients with mild injury, our observational study highlights substantial use of health-care resources and high mortality rates among patients with high-risk TIA or minor ischemic stroke assumed eligible for DAPT.